ডক্টর ইউনূসের দারিদ্র্য বাণিজ্য - উমর, বদরুদ্দীন, ১৯৩১- (ঢাকা : শ্রাবণ প্রকাশনী, 2011)
Articles on Muhammad Yunus, b. 1940, founder of Grameen Bank of Bangladesh and the corruption charges against him.
Donated By Akbar Ali Khan
In Bengali.
Keywords: Yunus, Muhammad, -- 1940-; Grameen Bank -- Corrupt practices; Development credit corporations -- Bangladesh; Microfinance -- Bangladesh; Rural credit -- Bangladesh